Accessible Communication of Corporate Social Responsibility: Development and Preliminary Evaluation of an Online Module. Issue 1 (March 2022) - Rossetti, Alessandra; Van Waes, Luuk
Communicating clearly about their socially responsible activities is becoming increasingly important for companies, as a growing number of stakeholders with different goals, knowledge, and language skills seek information on corporate social responsibility (CSR). Furthermore, the ability to communicate clearly is particularly appreciated in the workplace. To fill a gap in CSR communication training, this article describes the development and preliminary evaluation of an interdisciplinary and multimodal online module whose goal is to train Dutch-speaking business students in the production of accessible CSR content in English. After presenting our module, we discuss its implications for future training and for corporate communication.